THE IMPACT OF STRATEGIC ORIENTATION ON THE PERFORMANCE OF EMPLOYEES - Soulaf Abdalqadir Hameed Alsady; Almansour Ajeel Farhan Mansour Alsadoon (Scholars Digest Publishing, 2023)
This research was tested at the University of Maysan, and the research included the research methodology in terms of the problem, importance, and goals. The research also addressed the concept, importance, and dimensions of strategic direction represented by (strategic vision, strategic mission, strategic goals, organizational values), as well as presenting the concept, importance, and dimensions of employee performance represented by (Quality of work completed, commitment, quantity of work completed), as for the practical aspect, The simple random sampling method was used by the researcher to distribute the questionnaire forms to a sample of employees at the College of Nursing at the University of Misan, supposing that the community is homogeneous. An appropriate sample was chosen, in which 80 questionnaires were distributed to a sample of employees at the College of Nursing. Seventy-five valid questionnaires were retrieved for analysis, which expressed a response rate of 90%.
Keywords: The concept of strategic direction, The concept of employee performance, Strategic Vision.